PENGARUH MEDIA KONKRET PADA PEMBELAJARAN MATEMATIKA TERHADAP HASIL BELAJAR SISWA SDN 15 SEMPALAI TEBAS - Wirnawati, . (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract The problem in this research is â€œhow the influence of concrete media usage on mathematics learning on students learning outcomes of class III SDN 15 Sempalai districts Tebas?â€. This research has been used experiment method with quasi experiment and design research was nonequivalent control group design. The sample in this research was the third grade students of SDN 15 consisted of 23 students in class III B (control class) and 22 students in class III A (experiment class). Data collection tool was studentsâ€™ learning outcomes in the form of essay amounted to 9 questions. The result showed the average of final test result of the control class was 70,61 and the mean of final test result of experiment class was 82,23. Then, it was obtained that equal to 3,984 and with Î± = 5% and dk 43 equal to 1,682, mearning > , so is received. The conclusion exists influence of concrete media usageon mathematics learning on students learning outcomes of class III SDN 15 Sempalai districts Tebas. The counting of effect size (ES), got ES amounted to 0,72 (high category). Keyword: Influence, Concrete Media, Learning Outcomes